2018
DOI: 10.1016/j.apsusc.2018.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Improved biodegradability of Fe–Mn alloy after modification of surface chemistry and topography by a laser ablation

Abstract: In this study we report the influence of laser ablation on the controlled biodegradability of a Fe-Mn alloy developed for medical implants. After texturing by a nanosecond Nd:YAG laser, the surface expressed extreme super-hydrophilic wetting properties, since laser ablation led to micro-channels and chemical modification resulting in nanostructured metal oxides. The influence of functionalized surface properties on corrosion behaviour was examined on molecular level by using X-ray photoelectron spectroscopy. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Several studies have shown that the surface morphology and chemistry on micro- and nanoscale can be efficiently controlled also by femtosecond [7,8,9,10], picosecond [11] and nanosecond [12,13,14,15,16] laser pulses as well as by continuous wave (CW) lasers [17]. Such laser-induced micro-/nanostructuring leads to a significant improvement of the surface functionality and opens up completely new possibilities in the field of surface engineering [18] for a wide range of applications in photonics, tribology, wettability, heat transfer, and biomedicine [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the surface morphology and chemistry on micro- and nanoscale can be efficiently controlled also by femtosecond [7,8,9,10], picosecond [11] and nanosecond [12,13,14,15,16] laser pulses as well as by continuous wave (CW) lasers [17]. Such laser-induced micro-/nanostructuring leads to a significant improvement of the surface functionality and opens up completely new possibilities in the field of surface engineering [18] for a wide range of applications in photonics, tribology, wettability, heat transfer, and biomedicine [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Laser texturing of different materials, including glasses, semiconductors, polymers and metals enables the production of surfaces with superior wetting properties, which may be exhibited as extreme water repellency [19,25,26], self-healing [27], self-cleaning [28], anti-icing [29], reduced drag in laminar and turbulent flows [30], significantly enhanced heat transfer [31,32], improved corrosion resistance [33,34] and biodegradability [24]. The majority of these studies were made by ultrashort, i.e., pico-/femtosecond lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The function of oxidation on biological response is proved to be limited (as explained in details ins previous sections); however, oxidation by laser also can influence the degradation property in addition to topographical modifications. Donik et al [ 159 ] investigated the degradation property of laser textured Fe–Mn alloy (Mn-18 wt%). The samples after laser treatment showed an increased degradation rate, which is the result of both increased oxidation content and surface areas.…”
Section: Laser Surface Modification On Stents and Stent-related Materialsmentioning
confidence: 99%
“…However, this section also briefly presents a general concept of changing the surface wettability through the morphology and chemistry modification by laser-surface interaction. This concept isin addition to the boiling heat transferimportant also for biomedical [106,[120][121][122], corrosion [123][124][125][126], tribological [127][128][129][130], and fluid-flow [131] applications.…”
Section: Laser Surface Engineeringmentioning
confidence: 99%
“…12.9a) represents the simplest scanning strategy. Therefore, it was used in plenty of experiments, including the production of lasertextured hydrophobic surfaces for chemical sensing applications [114], laser texturing of wettability gradients [133], modifying the surface wettability for friction control [128] and the development of biodegradable materials by producing hydrophilic FeMn surfaces that trigger self-driven corrosion [121].…”
Section: Laser Texturing Of Two-dimensional Surfacesmentioning
confidence: 99%